2014
DOI: 10.1371/journal.pone.0082342
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Uric Acid, Cardiovascular and All-Cause Mortality in Peritoneal Dialysis Patients

Abstract: AimsTo investigate whether uric acid (UA) is an independent predictor of cardiovascular (CV) and all-cause mortality in peritoneal dialysis (PD) patients after controlling for recognized CV risk factors.MethodsA total of 2264 patients on chronic PD were collected from seven centers affiliated with the Socioeconomic Status on the Outcome of Peritoneal Dialysis (SSOP) Study. All demographic and laboratory data were recorded at baseline. Multivariate Cox regression was used to calculate the hazard ratio (HR) of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 43 publications
0
61
0
Order By: Relevance
“…An advanced age and menopausal status, [35,36] impaired renal uric acid excretion state, and sex hormonal dysfunction in the uremic status [37] may affect the SUA metabolism, although further studies are warranted to clarify this smaller sex difference of the SUA level and its mechanism. The relationship between the SUA level and mortality in those with ESRD has been explored in 5 HD cohorts [16,[19][20][21]38] and 3 PD cohorts, [25,26,39] and the results were diverse. Several studies showed that a low SUA level may be harmful against mortality, [16,[19][20][21]26] whereas others insisted that hyperuricemia increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…An advanced age and menopausal status, [35,36] impaired renal uric acid excretion state, and sex hormonal dysfunction in the uremic status [37] may affect the SUA metabolism, although further studies are warranted to clarify this smaller sex difference of the SUA level and its mechanism. The relationship between the SUA level and mortality in those with ESRD has been explored in 5 HD cohorts [16,[19][20][21]38] and 3 PD cohorts, [25,26,39] and the results were diverse. Several studies showed that a low SUA level may be harmful against mortality, [16,[19][20][21]26] whereas others insisted that hyperuricemia increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…130,131 However, in a recent observational study including 2264 PD patients, only a weak correlation of HUA with all-cause mortality could be detected. 132 The lack of large prospective studies in this field does not lead to reliable conclusions.…”
Section: Hua and CV Mortalitymentioning
confidence: 99%
“…And this kind of relationship only exists in male patients with diabetes [15][16][17]. Another study showed a weak prognostic value of UA in cardiovascular and all-cause mortality in PD patients generally [18]. The studies on the associations between UA and residual renal function (RRF) decline in PD patients showed a positive or "U-shaped" relationship [19,20].…”
Section: Introductionmentioning
confidence: 99%